Incidencia de la actividad combinada de banano y palma en el cálculo del anticipo de impuesto a la renta - Ojeda Aguirre, Lida Elizabeth (2015)
The objective of this project is to develop a guide using the guidelines of the legal regulations to determine the correct calculation of the advance of the Income Tax when you have combined efforts with the banana workers. The methodology that was used to carry out this work, it was the quantitative and the tools for collecting data were the interview to the counter in the Hacienda "Yamile" and the point to the financial information. Once implemented the tools, it was discovered to have financial statements with values separated both of banana as de palm as indicated by the Act of internal tax system. Within the job, in the chapter 1 lays down concepts and a bit of history about the taxes, income tax, banana and La Palma, also is drawn up the legal basis governing the banana activity; mentioned features of the company and sets out the main tax problems that owns the Hacienda. You choose one of those problems which are the reason for this project. In the next chapter, define a proposal for a solution and sets out objectives. It is proposed to carry out a Guide to which the counter of the Hacienda can rely to establish the correct calculation of the advance of the Income Tax, also performed a template designed in Excel as reinforcement to the guide. Within the third chapter, defines the viability of the project in their technical fields, economic, social and environmental. We conclude that taxes are necessary for the development of a country and help timely paying our obligations; the banana has a different tax treatment is why care should be taken when accounts are segregated as it could be misinterpreted as double counting.